THE ANALYSIS OF SOME PHYSIOLOGICAL VARIABLES IN TWO DIFFERENT TYPES OF HANDBALL TRAINING - Primož Pori; Maja Pori; Marko Zanoškar; Marko Šibila (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The purpose of the research paper was to establish, which energetic mechanisms are dominant in two different types of situational handball trainings and what kind of effort the players experience under those charges. Chosen exercises in handball training were activities of interval and continuous nature. With the use of measurements both in the sports hall and in physiological laboratory, the heart frequency, values of blood lactate and oxygen consumption were monitored.The sample of measured subjects was represented by 12 senior players from different attacking playing positions in the first handball league (average age 22.25 ± 2.5 let). The results of the study revealed that in the interval type of exercises the average absolute heart frequency was 136 beats per minute, the average value of blood lactate was 2,65 mmol/l, the proportion of relative oxygen consumption was 64.7 % of maximal oxygen consumption, the biggest proportion in relative heart frequency (HR % = (HR - HRrest)/(HRmax - HRrest) was below 50 % and between 70% and 90 % of maximal strain. The players spent in average 27 % of the playing time in areas between 5 % under and 5 % above anaerobic threshold. In exercises of continual nature we established, that the average absolute heart frequency was 130 beats per minute, the average value of blood lactate was 1,8 mmol/l, the share in relative oxygen consumption was 55,25 % of maximal oxygen consumption, the biggest share in relative heart frequency takes up strain between 50 and 70 % of maximal effort. It can be concluded that in chosen situational handball exercises the dominant type of effort is aerobic - anaerobic. In average, the exercises of interval nature required more effort from handball players.